Festas carnavalescas da elite de Porto Alegre : Evas e Marias nas redes do poder (1906-1914) - Leal, Caroline Pereira (2013)
This thesis investigates the changes that occurred in the Porto Alegre s carnival during the second cycle (1906-1914) of Esmeralda and Venetian carnival societies, highlighting the changes in relation to women's participation in the festivities. Will highlight the presence of members of the political and military elite within these associations and their possible influence on the changes. Show that the Evas give way to Marias, seeking a construction of a carnival distinct hierarchies and reinforcement of dominant males. In the first chapter, did a brief analysis of the trajectory of the two companies in the carnival of Porto Alegre since its foundation until its revival, highlighting the reasons why the press and the elite of the capital defended the need for a transformation of the festivities: the eradication of Shrovetide moralization and Carnival. The second chapter aims to evaluate the behavior and female participation during the celebrations, noting that in the second phase of these societies, women have gained greater exposure by participating in the board, organizing dances and having a prominent figure in Queens. However, this increased participation was conditioned to a moralization of his conduct. We noticed also that the influence of the participation of military and members of the Republican Party-Rio Grande on these companies was striking and that most women attending societies were daughters of the elite of the state capital, imbued with ideological conservatives and moral precepts, are therefore entangled amid the political power networks. In the last chapter, we studied the life histories of some of the queens of carnival societies Esmeralda and Venetians. Sought through analysis of individual trajectories corroborate what we had discussed earlier in stating that female participation in the carnival societies was permeated by political relationships and belonging to the military and political cadres of Porto Alegre. Finally, we analyze the carnival from the perspective of relationships that cross and transcend the world of dances and processions. In these celebrations, the daughters of the elite of the capital could have fun and connect with young families of good standing protected virulence and permittivity of Shrovetide. It was a carnival caste maidens, girls family, as in the carnival festivities elite Porto Alegre Eves of yore become the Marys.